Women's Resistance Towards Oppression in Etaf Rum's A Woman Is No Man - Frisky Nur Salvianny; Eka Nurcahyani (IAIN MADURA, 2020)
Women have been oppressed through the domination of patriarchy that controls their lives. Therefore, women resist the oppression by speaking up for their rights to own one’s life. This study investigates women's oppression and their resistance in the novel A Woman Is No Man by Etaf Rum. Deploying Patricia Hill Collins' theory of Matrix of Domination and Self-Definition, this study applied a descriptive-analytical method in analyzing how women experience oppression and their actions in resisting it. Portrayed by the three generations of Arab-American female characters, the result of this study finds women are experiencing oppressions managed within the four domains of power: structural, disciplinary, hegemonic, and interpersonal domain of power. While men have the privilege of being free, women are burden with the family’s reputation and domestic duties that turn them into a docile individual. Furthermore, women’s self-definition helps them to gather their self-worth to counter the oppression. Women’s resistances are realized through their ability to maintain self-valuation and respect, self-reliance and independence, and personal empowerment through the act of being brave in voicing their thoughts, going to college, and living on their own, and encouraging each other to raise awareness of self-definition